Surveillance of dialysis events: 12-Month experience at five outpatient adult hemodialysis centers in Kuwait - D.A. Badawy; H.S. Mowafi; H.H. Al-Mousa (Elsevier, 2014)
Summary: Background: Embedding dialysis surveillance scheme is associated with reductions in blood stream infection and antimicrobial consumption .The aim of this study was to establish baseline dialysis events (DE) rates; hospitalization, intravenous (IV) antibiotics start or a positive blood culture stratified by vascular access category and comparisons to published National Healthcare Safety Network (NHSN) rates. Methods: A retrospective review of DE was done between January to December 2012, in five outpatient adult hemodialysis center. Results: The pooled mean rates of hospitalization among patients with fistulas, grafts, permanent and temporary catheters were 2.8, 5.7, 5.1, and 10.6 per 100 patient-months, respectively. For positive blood culture the pooled mean rates were 0.2, 1.0, 1.9 and 2.7 per 100 patient-months in these groups. The IV antibiotics starts event pooled mean rates were 5.9, 9.0, 11.8, and 11.2 per 100 patient-months. DE were significantly more common in patients with permanent and temporary catheters when compared with patients with fistulas and graft (p < 0.001). Conclusion: Surveillance of DE rates in Kuwait revealed significantly lower mean rate of hospitalization and positive blood culture while IV antimicrobial start shows significantly higher mean rate when compared to published NHSN data. Keywords: Dialysis events, Surveillance, NHSN, Fistula, Graft